The comparison of efficacy and safety of nefazodone and amitriptyline in the treatment of major depressive disorder - Atmaca, Murad; Kulo?lu, Murat; Geçici, Ömer; Ünal, Ahmet; Firidin, Burak; Tezcan, A. Ertan (My University, 2001)
Objective: Nefazodone is a novel antidepressant whose efficacy has been demonstrated in the treatment of depression. The present study was planned to evaluate the efficiency and side effect profile of nefazodone, used recently in our country is psychiatry practice, comparing amitriptyline, an established drug in major depressive disorder. Method: The study consisted of the patients diagnosed as major depressive disorder according to the DSM IV criteria with above 18 Hamilton Depression Rating Scale (HDRS) score. The patients were randomly divided into two subgroups; nefazodone (n=19) and amitriptyline (n=19). All patients were assessed by HDRS, Hamilton Anxiety Rating Scale, Clinical Global Impression Scale. Results: Both nefazodone and amitriptyline were found to be efficacious. No patient in the nefazodone group, but two patients in the amitriptyline group, dropped out of the study because of experiencing adverse effect at the beginning of the study. In the nefazodone group, the most frequent adverse effects were weakness, sedation and nausea. However, in the amitriptyline group, those were anticholinergic and sexual side effects. Conclusion: In an eight week follow-up study, it was demonstrated that both nefazodone and amitriptyline were effective agents for the treatment of major depressive disorder and nefazodone was more tolerable compared to amitriptyline.
Major depresif bozukluk tedavisinde amitriptilin ve nefazodonun emniyet ve etkinliklerinin karşilaştirilmasi
Keywords: Amitriptyline; Major depressive disorder; Nefazodone